(3eONd GSJQGJjLj dJNWjW hJfejI GdehGQO GdHTQjI (B/s - (3MSf, QGhjIs ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2005)
(3GdEOGQI GdESJQGJjLjI ddehGQO GdHTQjI(B- (3GdESJKeGQ aj JfejI GdehGQO GdHTQjI(B- (3GSJQGJjLjGJ GdehGQO GdHTQjI aj Xd HYV GdJZjQGJ GdJfXjejIs
Keywords: (3GdJNWjWs; (3GdJfejIs; (3GdehGQO GdHTQjIs